A perspective on Drosophila genetics and its insight into human neurodegenerative disease - Bonini, Nancy M. (Frontiers in Molecular Biosciences, 2022)
Drosophila has been long appreciated as a classic genetic system for its ability to define gene function in vivo. Within the last several decades, the fly has also emerged as a premiere system for modeling and defining mechanisms of human disease by expressing dominant human disease genes and analyzing the effects. Here I discuss key aspects of this latter approach that first intrigued me to focus my laboratory research on this idea. Differences between the loss-of-function vs. the gain-of-function approach are raised—and the insight of these approaches for appreciating mechanisms that contribute to human neurodegenerative disease. The application of modifier genetics, which is a prominent goal of models of human disease, has implications for how specific genes or pathways intersect with the dominant disease-associated mechanisms. Models of human disease will continue to reveal unanticipated insight into fundamental cellular processes—insight that might be harder to glean from classical genetic methodologies vs modifier genetics of disease.